2020
DOI: 10.3174/ajnr.a6498
|View full text |Cite
|
Sign up to set email alerts
|

Signal of Carotid Intraplaque Hemorrhage on MR T1-Weighted Imaging: Association with Acute Cerebral Infarct

Abstract: BACKGROUND AND PURPOSE: Identifying the mere presence of carotid intraplaque hemorrhage would be insufficient to accurately discriminate the presence of acute cerebral infarct. We aimed to investigate the association between signal intensity ratios of carotid intraplaque hemorrhage on T1-weighted MR imaging and acute cerebral infarct in patients with hemorrhagic carotid plaques using MR vessel wall imaging. MATERIALS AND METHODS: Symptomatic patients with carotid intraplaque hemorrhage were included. The signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Since NIRS-derived LCBI can detect only pure LCP without IPH, it might influence the correlation between NIRS-derived LCBI and TOF-SIR. In other words, the lipid component without IPH in TOF-SIR would be indistinguishable from fibrous tissue with low- or iso-SIR because of theoretical signal attenuation, that is, IPH-containing lipids would present high SIR values in TOF-SIR due to the IPH signal [19, 22]. These results suggested that MR plaque imaging might overestimate thromboembolic risk during CAS because the amount of lipid in plaques containing IPH would be masked.…”
Section: Discussionmentioning
confidence: 99%
“…Since NIRS-derived LCBI can detect only pure LCP without IPH, it might influence the correlation between NIRS-derived LCBI and TOF-SIR. In other words, the lipid component without IPH in TOF-SIR would be indistinguishable from fibrous tissue with low- or iso-SIR because of theoretical signal attenuation, that is, IPH-containing lipids would present high SIR values in TOF-SIR due to the IPH signal [19, 22]. These results suggested that MR plaque imaging might overestimate thromboembolic risk during CAS because the amount of lipid in plaques containing IPH would be masked.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable plaque in the carotid artery is a critical cause of many cardiovascular diseases like stroke and ischemic attacks (Schinkel et al, 2020). Neovascularization and IPH contribute significantly to the rupture of atherosclerotic plaques (Van der Veken et al, 2016;Demeure et al, 2017;Yang et al, 2020). Wang et al (2020) found that increased carotid neovascularization was significantly related to aggravated cerebral white matter lesions in 269 participants based on CEUS.…”
Section: Discussionmentioning
confidence: 99%
“…Camps-Renom et al (2020) demonstrated that neovascularization was an independent predictor of ischemic stroke recurrence, based on 78 patients with carotid atherosclerosis. Literatures (Mark et al, 2020a,b;Yang et al, 2020) discovered that IPH had a close connection with a high risk of cardiovascular diseases. In addition, Teng et al (2012) found that the computed parameters of stress and strain in a carotid artery plaque increased as the distance between the neovessel and the artery lumen decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It will need to be clarified to which extent the thickness and percent stenosis degree of a hemorrhagic plaque influence its propensity to embolize, and further attention will be drawn on morphological aspects like IPH volume and intensity. 38 It also seems necessary to determine to which degree a hemorrhagic plaque develops inflammatory changes, e.g. through iron deposition, and following endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%